Tingkat Stres Siswa Menjelang Ujian Akhir Semester di SMAN 4 Denpasar - Wardana, Made Shanty; Dinata, I Made Krisna (E-Jurnal Medika Udayana; Vol 6 No 11 (2017): E-Jurnal Medika Udayana, 2017)
Stress is psychologic responses to various stressor that could happen for any people including 10th grade student who have stressor such as the last semester exam. The objective of this research is to study the stresses enhancement before the last semester exam at SMAN 4 Denpasar. This research used a cross-sectional study. Student of 10th grade was used as sample respondent and was interviewed in 2 time periods as follows: 1) on the one month before exam, and 2) on the three days before exam. The Depression Anxiety Stress Scale (DASS-42) questionnaire was used as instrument for interviews. Wilcoxon Test was used to know the enhancement of stresses for two periods. Descriptively, the results showed the enhancement of stresses level. However, analytically, the results showed that the level of stresses between 44 students in two different periods was not significantly different as indicated by the p value of 0.316 (p>0.05). Therefore, there was no significantly enhancement of student stresses before exam. Keyword : Stress, Last Semester Exam, Student